Role of management accountants in automotive supply chain management / Eley Suzana Kasim, Indra Devi Rajamanoharan and Normah Omar - Kasim, Eley Suzana; Rajamanoharan, Indra Devi; Omar, Normah (Penerbit UiTM (UiTM Press), 2016)
This study examines the role of management accountants in the supply chain management (SCM) of an automobile manufacturer. A case study was conducted on an automobile manufacturing firm operating in Malaysia. Drawing from SCM and management accounting literature and the Institute of Management Accountants' statements on management accounting (SMAs), this study argues that despite recommendations from professional accounting bodies, the role of management accountants in SCM processes remains limited. However, management accountants are involved in the SCM of the case firm in one of four capacities: as a 'planner', 'evaluator', 'controller' and 'verifier'. The results of this study provides additional insights into the contribution of management accountants to SCM as practiced within automotive manufacturing firms in Malaysia. Thus, this research adds to the body of knowledge on the integration of management accounting with SCM. Furthermore, it provides an opportunity to obtain increased understanding of how such an integration could be leveraged to enhance firm performance.